Influence of observer experience on cardiac magnetic resonance strain measurements using feature tracking and conventional tagging. (March 2018) - Feisst, Andreas; Kuetting, Daniel L.R.; Dabir, Darius; Luetkens, Julian; Homsi, Rami; Schild, Hans H.; Thomas, Daniel
Abstract: Aim: CMR quantitative myocardial strain analysis is increasingly being utilized in clinical routine. CMR feature tracking (FT) is now considered an alternative to the reference standard for strain assessment -CMR tagging. The impact of observer experience on the validity of FT results has not yet been investigated. The aim of this study was therefore to evaluate the observer experience-dependency of CMR FT and to compare results with the reference standard. Methods: CSPAMM and SSFP-Cine sequences were acquired in 38 individuals (19 patients with HFpEF, 19 controls) in identical midventricular short-axis locations. Global peak systolic circumferential strain (PSCS) together with LV ejection fraction (EF) and volumes were assessed by three observers (5, 3 and 0 years of CMR-strain experience). Intermodality, intra- as well inter-observer variability were assessed. Results: Correlation between tagging and FT derived PSCS depended on observer experience (r = 0.69, r = 0.58 and r = 0.53). For the inexperienced observer tagging and FT derived PSCS differed significantly (p = 0.0061). Intra-observer reproducibility of tagging derived PSCS were similar for all observers (coefficient of variation (CV): 6%, 6.8% and 4.9%) while reproducibility of FT derived PSCS (CV: 7.4%, 9.4% and 15.8%) varied depending on observer experience. Inter-observer reproducibility of tagging derived PSCS for observer 1 and 2 as well as 1 and 3 for tagging (CV: 6.17%, 9.18%) was superior in comparison to FT (CV: 11.8%, 16.4%). Conclusions: Reliability and accuracy of FT based strain analysis, more than tagging based strain analysis, is dependent on reader experience. CMR strain experience or dedicated training in strain evaluation is necessary for FT to deliver accurate strain data, comparable to that of CMR tagging.